Streamflow dynamics of Amazonian rivers according to their hydrogeochemical heterogeneity - Paulo Rodrigo Zanin; Rosane Barbosa Lopes Cavalcante; Rogério Ribeiro Marinho; Paulo Rógenes Monteiro Pontes (Journal of Hydrology: Regional Studies)
Study Region: Amazon and Tocantins-Araguaia watersheds. Study Focus: Watershed’s climatology and physiography are key drivers of hydrological processes, sediment yield, and river geochemistry. In the Amazon, rivers are traditionally classified into three hydrogeochemical types (whitewater, blackwater, and clearwater) based on their physicochemical characteristics. While this classification is well established, its relationship with streamflow dynamics remains largely unexplored. This study investigates whether distinct water discharge patterns exist among these river water types, offering insights into their environmental drivers. Specific streamflows and hydrological indexes derived from flow duration curves (1990–2019) of 106 river gauge stations distributed across the Brazilian Amazon were analyzed to characterize streamflow regimes. New Hydrological Insights for the Region: Monitored blackwater rivers have the highest runoff generation per unit area, while clearwater rivers have the lowest. The relative intensity of peak flow increment is the largest in monitored whitewater and clearwater rivers and the smallest in blackwater rivers. The proportion of baseflow contribution to streamflow is the largest in monitored clearwater rivers and the smallest in whitewater rivers. Precipitation is a strong driver of streamflow regimes, but physiographic factors, such as land cover and geology, also play an important role, particularly in baseflow and peak flow. Understanding these hydrological differences is crucial for assessing ecological flow requirements, ultimately aiding sustainable water resource management, and the relationships between river geochemistry and streamflow in the Amazon.